NEW TECHNOLOGIES FOR THE TREATMENT OF TYPE I DIABETES DURING PREGNANCY - Ольга Ивановна Мищенко; Елена Владимировна Рудаева; Вадим Гельевич Мозес; Кира Борисовна Мозес; Светлана Ивановна Елгина; Сергей Валерьевич Рыбников; Елена Германовна Рудаева; Татьяна Евгеньевна Помыткина (The Publishing House Medicine and Enlightenment, 2021)
New technologies are opening up promising opportunities for the treatment of type I diabetes during pregnancy. Recent evidence suggests that continuous glucose monitoring (CGM) should be offered to all women receiving intensive insulin therapy early in pregnancy, which records changes in blood glucose concentration every 5 minutes over a long period of time. Despite studies comparing insulin pump therapy with multiple daily injections of insulin, its effectiveness in reducing the incidence of hyperglycemia and hypoglycemia, lowering glycated hemoglobin (HbA1) levels, weight control and pregnancy outcomes remains unclear. Sensor-integrated insulin delivery (also called artificial pancreas or feedback insulin delivery) during pregnancy has been shown to improve time to goal and works well despite changing insulin requirements during pregnancy.